Deterministic teleportation of an arbitrary two-qubit state via a one-dimensional four-qubit cluster state. - Li, Hui; Li, Chunwen; Wu, Rebing
This paper presents an approach to deterministically teleport an arbitrary two-qubit state through a one-dimensional four-qubit cluster state serving as a probabilistic quantum channel. The channel is modulated in advance to avoid damage to the original states in this scheme, which is caused by the inevitable failure of constructing a channel between the sender and the receiver. The scheme is flexible because the channel can be modulated either by the sender or by the receiver, with the option of deciding whether the sender or the receiver modulates the channel, according to the distribution of the available particle resources. The efficiency can be improved by reusing previously discarded results that may lead to a faithful channel. The scheme can be uniformly performed, so the design process can be greatly simplified to realize a reliable deterministic teleportation. Finally, the scheme is extended to deterministic teleportation of an arbitrary n-qubit state in a generalized form.
Keywords: One-dimensional four-qubit cluster state; Atmospheric measurements